Penile Fracture-Report of Two Cases and Review of Current Literatures (Bangladesh Journal of Urology, 2020)
Penile fracture is an uncommon urological emergency especially in Bangladesh. The other name is traumatic rupture of the tunica albugenia and corpora cavernosa in erect penis. It occurs when an erect penis face to buckle under the pressure of a blunt sexual trauma. Patient gives the typical history of immediate detumescence, severe pain, swelling and eggplant deformity of the penile shaft due to penile injury. Immediate surgical exploration and repair of corpora Cavernosa with tunica albugenia is the most effective treatment modality. In normal cases diagnosis is made from history, physical examination alone. In some special cases ultrasonogram, radiological images, including retrograde urethrography or cavernosography are mandatory for proper diagnosis.Herein, we report 2 cases of penile fracture with review of current literature regarding treatment options.Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.98-102